2022
DOI: 10.3390/en15145294
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Pipeline in Emergency Operation and Assessing the Magnitude of the Gas Leak

Abstract: Accidents on gas pipelines cause significant damage to the national economy and the economy of the state. Thus, it is necessary to always be prepared for such situations in order to restore the normal operation of the gas pipeline as soon as possible. An important role is played by the execution time of the control actions to localize the accident, pump out the gas, and change the operating modes. It is essential that such control be undertaken, especially if such a situation occurs near a gas-measuring instal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…A practical example shows a reduction in the overshoot time. Compared to previously proposed methods [10,23,29,[73][74][75][76][77][78][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139], the time spent on equalizing the reservoir pressure is reduced by 15%. It is important to note not only the great theoretical significance of the research conducted, but also its real practical application.…”
Section: Discussionmentioning
confidence: 99%
“…A practical example shows a reduction in the overshoot time. Compared to previously proposed methods [10,23,29,[73][74][75][76][77][78][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139], the time spent on equalizing the reservoir pressure is reduced by 15%. It is important to note not only the great theoretical significance of the research conducted, but also its real practical application.…”
Section: Discussionmentioning
confidence: 99%
“…It makes it possible to construct a temperature dependence not from one single measurement location, but from all areas of the research object. Similar works were considered in [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106] but were applied to other objects. Thus, the logicality of the chosen research path was confirmed.…”
Section: The State Of Knowledge Of the Problemmentioning
confidence: 99%
“…The previous methods, such as ray and light diffraction, cannot be effectively detected (26,27). Some scholars believe that the previous testing methods for cracks in polyethylene pipes (28) have the problems of long testing time and complex testing process, which can not be continuously tested and affect the use of polyethylene pipes (29)(30)(31)(32). Therefore, finding an effective detection method for polyethylene pipeline cracks is a problem that needs to be solved at present, and it is also to avoid major economic losses and casualties caused by polyethylene pipelines (33,34).…”
Section: Introductionmentioning
confidence: 99%